Simulating coalitionally stable burden sharing agreements for the climate change problem - Johan Eyckmans; Henry Tulkens (Fondazione Eni Enrico Mattei (FEEM), 2001)
In this paper we introduce the CLIMNEG World Simulation (CWS) model for simulating cooperative game theoretic aspects of global climate negotiations. The model is derived from the seminal RICE model by Nordhaus and Yang (1996). We first state the necessary conditions that determine optimal investment and emission abatement paths under alternative cooperation regimes, and then we test empirically with a numerical version of the CWS model whether the cooperative game theoretic "core" property of the transfer scheme advocated by Germain, Toint and Tulkens (1997) holds. Under this transfer scheme no individual country, nor any subset of countries, should have an interest in leaving the international environmental agreement. For the numerical specification of the CWS model used here, we obtain the result that this is indeed the case.
Keywords: C71; C73; D9; D62; F42; Q2; 330; Environmental economics; climate change; burden sharing; simulations; core of cooperative games; Internationale Umweltpolitik; Umweltabkommen; Klimaschutz; Umweltökonomik; Klimawandel; Pareto-Optimum; Theorie